2018
DOI: 10.1111/apt.14636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HBV genotype and mutations on HBV DNA and qHBsAg levels in patients with HBeAg‐negative chronic HBV infection

Abstract: qHBsAg serum levels depend on the HBV genotype and together with HBV DNA levels on frequent mutations in PC, BCP and preS in HBeAg-negative patients. qHBsAg cut-offs when used as prognostic markers require genotype-dependent validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
5
33
0
2
Order By: Relevance
“…Based on the analysis of a large European cohort of HBV chronically infected patients, we identified an HBV genotype A mutant with a deletion of 15 aa (aa 25‐39 in the N‐terminal PreS1 domain . Western blot analysis of the serum of the patient using HBsAg‐specific antibodies did not show truncated LHBs, presumably due to the transcomplementation from integrated HBV‐DNA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of a large European cohort of HBV chronically infected patients, we identified an HBV genotype A mutant with a deletion of 15 aa (aa 25‐39 in the N‐terminal PreS1 domain . Western blot analysis of the serum of the patient using HBsAg‐specific antibodies did not show truncated LHBs, presumably due to the transcomplementation from integrated HBV‐DNA .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only few reports about the impact of N-terminal deletion in PreS1 on intracellular HBsAg localisation, HBsAg secretion and virus assembly. As the PreS1 exerts a variety of different functions in the viral life cycle, it is very crucial to investigate in detail how mutations in this part affect the virus life cycle.Based on the analysis of a large European cohort of HBV chronically infected patients, we identified an HBV genotype A mutant with a deletion of 15 aa (aa 25-39 in the N-terminal PreS1 domain 46,47. Western blot analysis of the serum of the patient using…”
mentioning
confidence: 99%
“…23 The ability of HBsAg decline to predict HBsAg loss may be affected by HBeAg status, HBV genotype, and the type/target of the treatment used. 23,25 Therefore, a decline in HBsAg levels in phase II clinical trials should currently only be considered as an exploratory and not a surrogate endpoint. A decline of HBsAg as a surrogate marker in phase III trials can only be accepted if it is demonstrated (i.e.…”
Section: Nomenclaturementioning
confidence: 99%
“…In their Editorial Alexopoulou and Karayiannis comment on our findings of the impact of the HBV genotype and frequent mutations on HBV DNA and qHBsAg levels in HBeAg‐negative chronic HBV‐infected patients . The authors of the Editorial point out that our data about qHBsAg levels might be of clinical relevance, as the qHBsAg seems not to be accurate enough in identifying inactive carriers, irrespective of their HBV genotype. Indeed, in our study qHBsAg levels vary significantly up to 1.4 log among the HBV genotypes A‐E.…”
mentioning
confidence: 91%